МЕТОДИКА ДИАГНОСТИКИ ПРЕДРАСПОЛОЖЕННОСТИ ЛИЧНОСТИ К КОНФЛИКТНОМУ ПОВЕДЕНИЮ - Нурымбетова, Э.Ж. (SCIENCE and SOCIETY, 2021)
In the presented article, the reliability of the methodology of a person's predisposition to conflict behavior has been studied. A complete presentation of the main results of the research are provided. As it is known, Thomas methodology identifies five types of behavior in a conflict situation: rivalry, cooperation, compromise, avoidance and adaptation.
Keywords: conflict situations; cooperation; rivalry; avoidance; compromise; adaptation